Emotional, Cognitive and Behavioral Reactions to Paranoid Symptoms in Clinical and Nonclinical Populations - Carvalho, Célia Barreto (2017)
Paranoia is a disruptive belief that can vary across a continuum, ranging from persecutory delusions presented in clinical settings to paranoid cognitions that are highly prevalent in the general population. The literature suggests that paranoid thoughts derive from the activation of a paranoid schema or information processing biases that can be sensitive to socially ambiguous stimuli and influence the processing of threatening situations.